P33 Outcomes of self-taken genital Neisseria gonorrhoeae culture swabs implemented to reduce direct patient contact during the Covid-19 pandemic. (16th June 2022) - Colver, Helen; Turner, Joelle
Abstract : Introduction: Obtaining samples of Neisseria gonorrhoeae for antibiotic sensitivity testing is important for purposes of antimicrobial stewardship. While urethral and cervical gonorrhoea culture samples are usually taken by a healthcare professional, the Covid-19 pandemic necessitated a reduction in direct patient contact. In our service, patients with confirmed gonorrhoea who did not otherwise require examination were asked to take their own urethral or vaginal culture swabs. Methods: GUMCAD coding was used to identify cases of cervical or male urethral Neisseria gonorrhoeae infection diagnosed on nucleic acid amplification testing, where the gonococcal culture result and the identity of the swab-taker (patient/healthcare professional) were recorded in the notes. 50 cases were selected in 2019, and 50 in 2020, after the onset of the Covid-19 pandemic. Proportions of patients taking their own swabs were calculated for the two periods. Culture positivity rates were compared between self-taken and healthcare professional-taken swabs. Results: During the pandemic, use of self-taken culture samples increased ten-fold. Although positivity for Neisseria gonorrhoeae was lower for self-taken swabs, 38% of male self-taken urethral samples tested positive for gonorrhoea, and the organism was successfully cultured from a self-taken vaginal swab on one occasion. Discussion: Although self-taken gonorrhoea cultures were less likely to grow Neisseria gonorrhoeae than those taken by healthcare professionals, they proved a useful tool in gathering sensitivity data in a time of restricted patient contact. The lower positivity rate of self-taken cultures may be partially attributable to their use in patients with fewer symptoms, and hence a lower bacterial load.